(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
This study examines the feminist perspective that Nadine Gordimer took in depicting the character of Julie Summers in her novel The Pickup. In the following research, a textual analysis of the aforementioned novel is presented in an effort to bring attention to the conflict that exists between society and the feminine individual. Gordimer places Julie in a position in The Pickup where she is forced to make a choice between doing what she wants and living up to the expectations of society for women. Because she is a female protagonist living in a patriarchal culture, Julie is required to plot out the path of her life in order to be successful in overcoming a number of challenges. In a nutshell, Gordimer’s feminist approach will be evaluated in terms of her capacity to interweave the social and cultural circumstances prevailing in the two distinct communities in which the protagonist resides with the protagonist’s capacity to overcome all obstacles in order to alter the stereotypical image of women in both communities. This evaluation will take place in terms of Gordimer’s ability to interweave the social and cultural circumstances prevailing in the two distinct communities in which the protagonist resides. Julie’s resistance to being governed by the traditional codes that govern her South African community is another topic that is investigated in this study. Another topic that is investigated is Julie’s desire to adapt to the culture and religion of her lover’s community, which is located in a distant nation. When the main female character, represented here by Julie, makes the decision to live a life that is nonconformist to the prevalent societal and cultural norms regarding marriage and motherhood, the purpose of this study is also to investigate the various forces that may conspire against the particular female character in question. In addition to this, the purpose of the study is to determine Gordimer’s viewpoint on the predicament faced by the contemporary African woman as a direct result of her defiance of the conventional cultural and social norms. In this instance, Julie is a model for subverting the traditional image of a woman who is capable of beginning significant societal change. Julie is a model for subverting the traditional image of a woman.